Efektivitas Pendekatan Cognitive Behaviour Therapy (CBT) untuk Mengurangi Tingkat Glossophobia pada Siswa di MTs Maftahul Huda - Rofiqoh, Firda Maratur; Rahmawati, Weni Kurnia; Fauziyah, Nailul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Public speaking anxiety, commonly referred to as glossophobia, is a manifestation of social phobia frequently experienced by students at the secondary education level. This condition may hinder students’ communication skills, academic participation, and the development of self-confidence. Therefore, effective and evidence-based counseling interventions are required to help students manage such anxiety. This study aimed to examine the effectiveness of Cognitive Behavior Therapy (CBT)-based counseling services in reducing public speaking anxiety among eighth-grade students at a Madrasah Tsanawiyah (MTs). A quantitative approach was employed using a quasi-experimental design with a pretest–posttest control group model. The research participants consisted of 16 students selected through purposive sampling and assigned to either an experimental group or a control group. Data were collected before and after the intervention using a glossophobia questionnaire developed based on three main aspects: physiological, psychological, and behavioral. Data analysis was conducted to compare anxiety scores before and after the intervention. The results indicated a significant difference between pre-test and post-test scores in the experimental group, with a significance value of p = 0.048 (p < 0.05). The experimental group showed a substantial decrease in glossophobia scores, from a mean of 72.62 to 38.88, while the control group experienced only a slight reduction from 84.63 to 43.50. These findings demonstrate that CBT-based counseling services are significantly effective in reducing public speaking anxiety among students. The results provide important implications for school guidance and counseling practices, particularly in implementing CBT interventions to help students manage glossophobia in a more adaptive manner.